Optimising Digital Public Relations in the Transformation of Smart and Sustainable City Communication: A Case Study of Jakarta and Bandung - Yulia, Irla; Fajrini, Nurkhalila; Mulyajati, Enggar (Indonesian Scientific Publication, 2025)
The present study analyses the strategic role of digital public relations (PR) in supporting the transformation of public communication towards Smart Sustainable Cities (SSCs) in Jakarta and Bandung. Using a qualitative case study approach, data were collected through interviews, digital media observation, and analysis of official smart city platforms. Thematic analysis was used to identify key patterns. Findings reveal that both cities use super-apps and social media to improve efficiency, transparency, and digital engagement. Challenges include human resource limitations, low digital literacy among certain groups, one-way communication dominance, and suboptimal system integration. Opportunities arise from the strong digital infrastructure and widespread social media. The study concludes that strengthening human capacity, targeted literacy programs, and interactive communication strategies are essential for effective digital PR in SSCs.